2011
DOI: 10.3389/fpsyg.2011.00123
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Attentional Networks in Early and Late Bilinguals: The Role of Age of Acquisition

Abstract: Previous studies have demonstrated a bilingual advantage in the efficiency of executive attention. A question remains, however, about the impact of the age of L2 acquisition and relative balance of the two languages on the enhancement of executive functions in bilinguals, and whether this is modulated by the similarity of the bilingual's two languages. The present study explores these issues by comparing the efficiency of attentional networks amongst three groups of young adults living in Australia: English mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
211
5
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(242 citation statements)
references
References 84 publications
(131 reference statements)
22
211
5
4
Order By: Relevance
“…Genesee et al (2004) and McLaughlin (1984) classify people who acquired a second language beyond the age of three as later bilinguals (LBL). Whereas, some researchers refer to people exposed to two languages within the first year of life as simultaneous bilinguals and people who acquire a second language prior to school entry as early bilinguals (EBL) (De Houwer 2005).There is some evidence showing that AoA of L2 has potential effects on EF sub-processes among BL (Chee et al 2001;Toa et al 2011;Luk et al 2011). For example, Luk et al (2011) divided young adult BL into early versus late groups based on the age at which participants reported becoming actively bilingual (i.e., speaking two languages daily).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Genesee et al (2004) and McLaughlin (1984) classify people who acquired a second language beyond the age of three as later bilinguals (LBL). Whereas, some researchers refer to people exposed to two languages within the first year of life as simultaneous bilinguals and people who acquire a second language prior to school entry as early bilinguals (EBL) (De Houwer 2005).There is some evidence showing that AoA of L2 has potential effects on EF sub-processes among BL (Chee et al 2001;Toa et al 2011;Luk et al 2011). For example, Luk et al (2011) divided young adult BL into early versus late groups based on the age at which participants reported becoming actively bilingual (i.e., speaking two languages daily).…”
Section: Introductionmentioning
confidence: 96%
“…Luk et al (2011) reported a positive correlation between onset age of bilingualism and the flanker effect, such individuals who began using two languages at younger ages demonstrated a smaller flanker effect (i.e., better inhibition) compared to individuals who began speaking a second language later. Furthermore, Toa et al (2011) compared performance on the Lateralized Attention Network Test (LANT; Green and Abutalebi 2008), a computerized flanker task, among adult bilinguals who had acquired an L2 before age 6 (EBL), adult BL who acquired an L2 between 12 and 19 years of age (LBL) and ML. Based on their performance on the LANT, EBL responded significantly faster on all trial types (i.e., congruent and incongruent) compared to ML.…”
Section: Introductionmentioning
confidence: 99%
“…Such late bilinguals (who acquired their second language beyond puberty) are the focus of the present investigation. Not only are studies investigating language and cognitive control in late bilinguals scarce, but those studies that do exist (typically involving college-aged late bilinguals) are far from uniform in their outcomes (Luk, Bialystok, Craik & Grady, 2011;Tao, Marzecová, Taft, Asanowicz, & Wodniecka, 2011, Festman & Münte, 2012: while some work has found cognitive advantages for late bilinguals in their twenties, other studies have not or only partially revealed such an advantage. The question of whether the bilingual cognitive advantage applies across the full range of ages of acquisition thus remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The work that does exist is highly variable in its outcome. Tao et al (2011) looked at three groups of young adults in Australia: a monolingual English group as well as two bilingual groups (one consisting of early and the other of late Chinese-English bilinguals). Both bilingual groups were found to have denser and more efficient executive function networks than the monolinguals, but there were intergroup differences between the bilinguals: whereas the early bilinguals appeared better at monitoring tasks, late bilinguals' superior performance lay especially in conflict monitoring, both assessed by means of a lateralized attention networks test.…”
Section: The Bilingual Advantagementioning
confidence: 99%
“…Flanker task, Eriksen & Eriksen, 1974), such bilingual advantage over monolingual performance has been reported many times over the years since the first report (e.g. Costa, Hernandez, Costa-Faidella, & Sebastian-Galles, 2009;Costa, Hernandez, & Sebastian-Galles, 2008;Kapa & Colombo, 2013;Tao, Marzecova, Taft, Asanowicz, & Wodniecka, 2011).…”
Section: Evidence For and Against Bilingual Advantagementioning
confidence: 99%